Desafios da educação pedagógica permanente do médico para o exercício da docência - Matarucco, Cristina Rocha (2018)
Introduction: It is crucial to implement continuous professional development in universities to develop skills and competencies in doctors who are professors taking into account the new curricular guidelines and the increasing opening of new medicines courses. Objective: Analyze the continuous professional development of professors of the medicine course of Centro Universitário de Votuporanga (UNIFEV); identify potentialities and difficulties in the continuous professional development of professors of the medicine course of UNIFEV; verify the applicability of such development in the teaching process and propose improvements in the continuous professional development of professors of the medicine course of UNIFEV. Methodology: Descriptive quantitative research with nine doctors who are professors that participated in the teaching training program of UNIFEV using guiding questions and reports obtained in the focus group. The reports were analyzed by means of the content analysis methodology. Results: Time constraints, the lack of previous scheduling, recognition and motivation, as well as the absence of a minimum require attendance were some of the aspects identified as obstacles for the participation in continuous professional development. The facilitating aspects were: the use of new methodologies, the exchange of experiences, the opportunity and need of learning among others. The applicability was in the field of the different active methodology techniques and of the evaluation of the teaching-learning process. The contributions for the improvement of continuous professional development were related to scheduling and feedback of its applicability. Conclusion: The continuous pedagogical development for professors has contributed to the medicine course. Based on the results, we suggest changing schedules according to doctor’s availability, incorporating hybrid teaching and addressing specific themes according to professors’ needs